Portraying Patron-client in Fishermen Work Relationships: A Phenomenon from Bengkulu, Indonesia - Adisel Adisel; Suryati Suryati; Riswanto Riswanto (Faculty of Social and Political Sciences - UIN Walisongo Semarang, 2023)
The working pattern in traditional society still becomes an exciting topic to investigate as they portray how society makes their living. The research aims at investigating the relationship between employer and employee in fishing management in Kelurahan Pasar Bengkulu, Bengkulu Province, Indonesia. The study employed a phenomenology-based qualitative approach, with participants chosen using a purposive sampling technique. Data were gathered through observation, interviews, and documentation. The collected data were analyzed by reducing, describing, and verifying data. The standards of credibility, transferability, dependability, and confirmability are confirmed to validate the data. The findings signified that:1) the patron-client symbolizes exploitation in which most business is dominated by the middlemen, while the fishermen only play a role as the executors during the fishing process. Additionally, the patron-client relationship represents an imbalance of fishery profit sharing; 2) such a relationship does contribute to fishermen’s structural and cultural poverty. The cooperation between labor associations and governance active role supported by financial aid from related parties is highly recommended to promote fishermen’s wealth.